A Millimeter Wave Antenna using Slots for Defense Applications - Negi, Deepa; Khanna, Rajesh (International Journal of Engineering and Technology, 2018)
In this paper, a rectangular dual band millimeter wave (MMW) microstrip antenna using U and circular slot is designed for defense applications. The antenna operates in the (57-64) GHz unlicensed frequency band. The proposed antenna is designed using RT/duroid substrate having dielectric constant 2.3, thickness 0.04mm and strip line feeding technique. The proposed antenna results are simulated and optimized using Computer Simulation Technology (CST) simulation software. The maximum return loss achieved is -15dB and -25.45 dB respectively for both U and circular slot. Simulation results show that the antenna having circular slot gave better results. The antenna simulation results such as return loss, gain and directivity are presented in this paper.Â